Strengthening Bumdes through Customer Satisfaction and Loyalty as the Defense of the Bumdes Business in Indonesia Post-Covid-19 - Muhammad Amin Nasution; Zulkifli Musannip Efendi Siregar; Pristiyono Pristiyono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the direct effect of product quality and service quality variables on customer satisfaction which is moderated by customer loyalty as well as a source of internal strength for the Mekar Sari Village Business Unit in running its business, another goal that is expected from this research is the Mekar Sari Village Community Enterprise as a company owned by the village community, especially the managers. Bumdes Mekar Sari that product quality, service quality, customer satisfaction, and customer loyalty are important factors in marketing and become a benchmark for determining the success of a refill drinking water depot business. This research includes quantitative descriptive research, the sample in this study is a loyal customer of Bumdes Mekar Sari Selat Besar Village which has been a member for 1 year as many as 130 customers, the determination of the sample in this study applied purposive sampling. Collecting data in this study using primary data (questionnaire) which contains questions regarding the indicators of product quality, service quality, customer satisfaction, and customer loyalty variables. To solve the problems studied, data analysis techniques used path analysis with SPSS and AMOS applications. From the results of research and hypothesis testing, it was found that product quality has a direct effect on customer satisfaction, service quality has a direct effect on customer satisfaction, and customer satisfaction has a direct effect on customer loyalty. Product quality has an indirect effect on customer loyalty through customer satisfaction. Service quality has an indirect effect on customer loyalty through customer satisfaction.